Population simulation model of Sitophilus zeamais (Coleoptera: Curculionidae) in grain stores in West Africa - Meikle, W.G.; Holst, N.; Markham, R.H. (Oxford University Press, 1999)
The biology of Sitophilus zeamais Motschulsky, an important pest of stored commodities, is well described in the literature. To integrate current knowledge and to understand better the population dynamics of this species in rural maize, Zea mays L., stores, we developed a distributed-delay, demographic simulation model. Published equations describing the effects of temperature, humidity, and density effects on fecundity, juvenile survivorship and development and emigration were used or equations were estimated from published data and from laboratory experiments. Simulation model output was compared with S. zeamais density observed in field experiments before and after the introduction of Prostephanus truncatus (Horn) to West Africa. The overall phenology of the simulated beetle dynamics reflected that of field data, although the model output tended to overestimate beetle population growth early in the season. The model was modified using published data to simulate dynamics of populations developing on resistant and susceptible maize cultivars. The model is intended as part of a cost-effective tool for evaluating factors influencing population dynamics of stored-product pests and their natural enemies and to provide a framework for assessing different control strategies in an integrated control context.